Imaging and Analysis of Layered Crust and Upper Mantle Structures on Earth and Mars - Zhāng, Quán (Université d'Ottawa | University of Ottawa, 2026)
Seismological imaging provides quantitative constraints on the layered structure and dynamics of Earth and other terrestrial planets (e.g., Mars) by leveraging seismic-wave propagation, scattering, and mode conversion to infer elastic properties, density structure, and discontinuity topography. Because the crust and upper mantle host the most active tectonic processes—subduction, lithospheric deformation, and mantle upwelling—their signatures are strongly expressed in teleseismic waveforms and can be interrogated using correlation-based approaches, tomography, and receiver functions to resolve lateral heterogeneity and depth-dependent interfaces. This thesis presents four manuscript-style studies that quantify the structure, thermal state, and dynamical coupling of the crust and upper mantle across contrasting tectonic settings on Mars, New Zealand, and western Canada. The first study develops a reference seismic velocity model for the Martian crust and lithosphere through joint inversion of multi-component correlation spectra from the InSight station over a limited observation interval, constraining near-station layering and informing interpretations of present-day lithospheric activity. The second study integrates a new crustal thickness model with a density-structure framework to assess the thermal contribution to high topography in the western Canadian Cordillera and to infer a moderately depleted cratonic mantle lithosphere relative to North American reference structure, emphasizing coupled thermal effects across the crust–mantle system. The remaining two studies target the mantle transition zone, whose bounding discontinuities provide sensitive constraints on temperature and composition. In New Zealand, receiver-function results indicate mantle transition zone thinning beneath central North Island and signatures of hot upwelling beneath Northland and the Great South Basin, consistent with thermal anomalies associated with subduction and arc volcanism. In western Canada, coherent depressions of both the 410- and 660-km discontinuities aligned with slab-window geometry require a warm mantle transition zone and a warmer-than-average uppermost lower mantle estimated by Monte Carlo approach, implying that a fossil ridge–slab-window system can channel deep-mantle heat upward and contribute to long-term Cordilleran uplift. Together, these studies provide an observation-driven synthesis of how thermal and compositional heterogeneity within the lithosphere and mantle transition zone governs tectonic evolution and mantle convection on Earth and Mars.
Keywords: Seismic imaging; Crust and upper mantle structures